2016
DOI: 10.1002/2016jd026006
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of δ13C in CH4 and using particle dispersion modeling to characterize sources of Arctic methane within an air mass

Abstract: A stratified air mass enriched in methane (CH4) was sampled at ~600 m to ~2000 m altitude, between the north coast of Norway and Svalbard as part of the Methane in the Arctic: Measurements and Modelling campaign on board the UK's BAe‐146‐301 Atmospheric Research Aircraft. The approach used here, which combines interpretation of multiple tracers with transport modeling, enables better understanding of the emission sources that contribute to the background mixing ratios of CH4 in the Arctic. Importantly, it allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 67 publications
2
31
0
Order By: Relevance
“…[]. The isotopic signature of −71‰ is similar to the signature of methane released in ebullition from northern Siberian lakes (−70‰ [ Walter et al ., ]), wetland emissions in western Siberia (−70‰) [ Umezawa et al ., ], and long‐range transported methane to the Arctic from northern Russia [ France et al ., ], suggesting that this isotopic signature may be representative of boreal wetland emissions, but this should be verified by aircraft campaigns over other regions in which wetlands emissions dominate. New measurements in Canadian wetland regions have been made using the diel sampling technique for comparison (see supporting information).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[]. The isotopic signature of −71‰ is similar to the signature of methane released in ebullition from northern Siberian lakes (−70‰ [ Walter et al ., ]), wetland emissions in western Siberia (−70‰) [ Umezawa et al ., ], and long‐range transported methane to the Arctic from northern Russia [ France et al ., ], suggesting that this isotopic signature may be representative of boreal wetland emissions, but this should be verified by aircraft campaigns over other regions in which wetlands emissions dominate. New measurements in Canadian wetland regions have been made using the diel sampling technique for comparison (see supporting information).…”
Section: Discussionmentioning
confidence: 94%
“…At 100 m above the wetlands, the aircraft measurements showed the same signature over wide tracts of wetland in well‐characterized air masses. This signature could also be identified in far‐traveled air arriving after multiday transport at the remote Zeppelin station [ Fisher et al ., ] and also sampled in air over the Arctic Ocean [ France et al ., ] in air transported from Siberia. The Canadian diel results found that the methane was slightly more enriched at −67 ± 1‰, but these measurements were at lower latitudes (54°21′N and 49°53′N) on the southern fringe of the boreal forest.…”
Section: Discussionmentioning
confidence: 99%
“…[]. For a more detailed breakdown of source signatures, see, e.g., France et al [] and Zazzeri et al [].…”
Section: Resultsmentioning
confidence: 99%
“…A further possibility is that various mainland and offshore sources have already been well mixed by the time we sampled the air. For example, an approximation of the bulk signature of multiple sources that have mixed together can be made using the following equation [ France et al , ]: δ13Cbulk=δ13Cx[X%]+δ13Cy[Y%], where δ 13 C bulk is the bulk signature (as determined by the Keeling plot), and X and Y represent different component sources of CH 4 . In this case, a simple calculation can be made to test whether a mixture of land‐based emissions could combine with gas rig emissions to plausibly generate the observed bulk signature of −52‰.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation